The credit guarantee in terms of the National Credit Act 34 of 2005 : an instrument promoting small and medium enterprises' access to credit - Renke, Stefan (University of Pretoria, 2023)
Mini Dissertation (LLM (Banking Law))--University of Pretoria, 2022.